An in-situ method of identifying ingredients of zeotropic refrigerants by inversion problem technique. Issue 4 (16th March 2019) - Zhang, Ji; Yuan, Han; Mei, Ning; Li, Yan; Si, Hongyu; Cao, Peichun
ABSTRACT: An inversion method is applied to identify ingredients of zeotropic refrigerants in a circular duct. In the case of low Reynolds number and constant fluid pressure, the temperature distribution of direct heat transfer problem can be solved numerically. The thermophysical parameters of zeotropic refrigerants are determined by using inversion problem technique, the ingredients of refrigerants can be identified eventually. An in-situ experimental apparatus was proposed and three test samples with different composition refrigerants were conducted in this study. The experiment results show that the relative error of ingredients identification can be limited within 8.33%.